VD_FINDINFO Jug / 2013 / 42 vom 12. Februar 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 227 CPP (CH), 229 al. 3 let. b CPP (CH)